Saxotronic Funk for Alto Saxophone A Creative Research in Music Composition - Pruksavanich, Wisuwat (Rangsit Music Journal, 2023)
This creative music research on Saxotronic Funk for alto saxophone aims to present saxophone extended techniques, such as Slap-Tongue and Multiphonic through the combination of electronic and funk musical style. The author conducted the research by analyzing saxophone extended techniques and applying these techniques in the composition. The author found that to apply saxophone extended techniques in the piece Saxotronic Funk for alto saxophone comprised Slap-Tongue and Multiphonic techniques. The said techniques led into the unique sound and timbre of the saxophone and demonstrated the saxophone in the electronic and funk musical style.